Development of E-Module based on Heyzine Flipbook to Increase Student Motivation and Learning Outcomes in Learning Letters - Februardi Maulana Putra; Laily Nurlina (JINoP (Jurnal Inovasi Pembelajaran), 2025)
This study examines the effect of using Heyzine Flipbooks on students' motivation and learning outcomes in learning letter text for grade VII students at SMP Negeri 2 Padamara. With a quantitative experimental approach, two groups were analyzed: the control group (class 7A) using conventional learning methods, and the experimental group (class 7D) using Heyzine Flipbooks as an interactive learning tool. The purpose of this study was to examine the effect on the use of Heyzine Flipbooks on student motivation and learning outcomes. The research method used in this study is to use a quantitative method approach with experimental methods. Pretest and post-test data were collected to measure students' motivation and learning outcomes. The results showed a significant increase in motivation and learning achievement in the experimental group compared to the control group. The use of Heyzine Flipbooks, which integrates multimedia elements such as videos, images, and animations, provides a more interesting and interactive learning experience. It allows students to better understand the subject matter and participate more actively in the learning process. This study concludes that Heyzine Flipbooks is an effective digital tool to improve students' motivation and learning outcomes, especially on materials that require complex understanding such as letter texts.